Correlates of Adoption of Package of Practices in Bt Cotton by the Farmers of Ranga Reddy District of Andhra Pradesh - Deepthi. V , Hema. B , Kiranmayi. K; Jyothi. V (Indian Journal of Extension Education, 2014)
The study was taken up with the main objective to study the correlates of the adoption of the recommended package of practices in Bt cotton by the farmers of Ranga Reddy District of Andhra Pradesh and their profile characteristics. For the purpose of study fifty (50) farmers growing Bt cotton were selected at random from Kethireddypalli village of Moinabad mandal of Ranga Reddy district of Andhra Pradesh. The data was collected during 2013 through structured interview schedule. The independent variables studied included age, education, family type, land holding, farming experience, training, extension contact, sources of information, social participation, market orientation, economic orientation, risk orientation, input availability and labour availability for cultivation of Bt cotton. While the dependent variable studied included ’adoption of package of practices in Bt cotton. The adoption showed positive and significant correlation with training, sources of information and input availability at 5 per cent level of significance. The dependent variable also showed positive and significant correlation with labour availability at 1per cent level of significance.